Rich litter admixture effects on belowground carbon dynamics in temperate forests: From leaf litter input to molecular composition of soil organic matter - S.E. Nijdam; K. Vancampenhout; B. Jansen; E. Morriën; J. Schellekens; B. Leenders; J. Simons; L. Van den Berg; M. de Graaf; B. Nyssen; B. Muys; E. Desie (Forest Ecology and Management, 2026)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Environmental drivers of planted seedling performance in a Zambian Miombo woodland restoration area - S. L. Maes; C. Beers y Moreno; M. P. Perring; B. Muys (New Forests, 2025)

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Disentangling drivers of litter decomposition in a multi-continent network of tree diversity experiments - Ellen Desie; Juan Zuo; Kris Verheyen; Ika Djukic; Koenraad Van Meerbeek; Harald Auge; Nadia Barsoum; Christel Baum; Helge Bruelheide; Nico Eisenhauer; Heike Feldhaar; Olga Ferlian; et al. (Science of The Total Environment, 2023)

Tree diversity effects on soil microbial biomass and respiration are context dependent across forest diversity experiments - Simone Cesarz; Dylan Craven; Harald Auge; Helge Bruelheide; Bastien Castagneyrol; Jessica Gutknecht; Andy Hector; Hervé Jactel; Julia Koricheva; Christian Messier; Bart Muys; Michael J. O’Brien; et al. (Global Ecology and Biogeography, 2022)
Aim Soil microorganisms are essential for the functioning of terrestrial ecosystems. Although soil microbial communities and functions are linked to tree species composition and diversity, there has been no comprehensive study of the generality or context dependence of these relationships. Here, we examine tree diversity–soil microbial biomass and respiration relationships across environmental gradients using a global network of tree diversity experiments. Location Boreal, temperate, subtropical and tropical forests. Time period 2013. Major taxa studied Soil microorganisms. Methods Soil samples collected from 11 tree diversity experiments were used to measure microbial respiration, biomass and respiratory quotient using the substrate‐induced respiration method. All samples were measured using the same analytical device, method and procedure to reduce measurement bias. We used linear mixed‐effects models and principal components analysis (PCA) to examine the effects of tree diversity (taxonomic and phylogenetic), environmental conditions and interactions on soil microbial properties. Results Abiotic drivers, mainly soil water content, but also soil carbon and soil pH, significantly increased soil microbial biomass and respiration. High soil water content reduced the importance of other abiotic drivers. Tree diversity had no effect on the soil microbial properties, but interactions with phylogenetic diversity indicated that the effects of diversity were context dependent and stronger in drier soils. Similar results were found for soil carbon and soil pH. Main conclusions Our results indicate the importance of abiotic variables, especially soil water content, for maintaining high levels of soil microbial functions and modulating the effects of other environmental drivers. Planting tree species with diverse water‐use strategies and structurally complex canopies and high leaf area might be crucial for maintaining high soil microbial biomass and respiration. Given that greater phylogenetic distance alleviated unfavourable soil water conditions, reforestation efforts that account for traits improving soil water content or select more phylogenetically distant species might assist in increasing soil microbial functions.

Reviewing the Use of Resilience Concepts in Forest Sciences - L. Nikinmaa; M. Lindner; E. Cantarello; A. S. Jump; R. Seidl; G. Winkel; B. Muys (Current Forestry Reports, 2020)

Correction to: Root tensile strength and root distribution of typical Mediterranean plant species and their contribution to soil shear strength - S. De Baets; J. Poesen; B. Reubens; K. Wemans; J. De Baerdemaeker; B. Muys (Plant and Soil, 2018)

Leaf area index development in temperate oak and beech forests is driven by stand characteristics and weather conditions - R. Bequet; M. Campioli; V. Kint; D. Vansteenkiste; B. Muys; R. Ceulemans (Trees, 2011)

Root tensile strength and root distribution of typical Mediterranean plant species and their contribution to soil shear strength - S. De Baets; J. Poesen; B. Reubens; K. Wemans; J. De Baerdemaeker; B. Muys (Plant and Soil, 2008)

AFFOREST sDSS: a metamodel based spatial decision support system for afforestation of agricultural land - S. Gilliams; J. Van Orshoven; B. Muys; H. Kros; G.W. Heil; W. Van Deursen (New Forests, 2005)

Carbon sequestration following afforestation of agricultural soils: comparing oak/beech forest to short-rotation poplar coppice combining a process and a carbon accounting model - G. Deckmyn; B. Muys; J. Garcia Quijano; R. Ceulemans (Global Change Biology, 2004)

Carbon sequestration following afforestation of agricultural soils: comparing oak/beech forest to short‐rotation poplar coppice combining a process and a carbon accounting model - G. Deckmyn; B. Muys; J. Garcia Quijano; R. Ceulemans (Global Change Biology, 2004)
To compare the benefits for carbon (C) sequestration of afforestation with a multifunctional oak–beech forest vs. a poplar short‐rotation coppice (SRC), model simulations were run through a serial linkage of a mechanistic model and an accounting model. The process model SECRETS (Stand to Ecosystem CaRbon and EvapoTranspiration Simulator) was used to predict growth, C allocation and soil C. The output from SECRETS was used as an input for the C accounting model GORCAM (Graz Oak Ridge Carbon Accounting Model) yielding data on C sequestration in wood products, substitution of wood fuel for fossil fuel and total CO 2 emission reduction. Such C accounting based on a process model enables a more realistic calculation of forest growth, litter decomposition and soil processes. Moreover, it allows simulating the influence of climate change on the C budget. Net primary production of an oak–beech forest is low, a stable 2.5 t C ha −1 yr −1 after 150 years, compared to 6.2 t C ha −1 yr −1 for a SRC plantation. But while the yield from the SRC poplar is used as fuel and thus returns quickly to the atmosphere, the yield from the oak‐beech forest is used in long‐lasting wood products. The total C pool in the mixed forest (living biomass, wood products and soil) after 150 years amounts to 324 t C ha −1 compared to 162 in the poplar coppice. However, when account is taken of the energy substitution, coppice culture reduces emissions with 24.3–29.3 t CO 2 ha −1 yr −1 while the mixed forest reduces only 6.2–7.1 t CO 2 ha −1 yr −1 . These results demonstrate the added value of combining detailed process models with C‐accounting models to improve the predictive capacity of model simulations.

Increase of biodiversity in homogeneous Scots pine stands by an ecologically diversified management - N. Lust; B. Muys; L. Nachtergale (Biodiversity and Conservation, 1998)